(untitled) (Eurasian Research Bulletin, 2023)
Models of a monolithic foundation plate and the ground beneath them were created in order to study the performance of a vertical armo-element (VAE). The article examines the radius of horizontal pressure distribution as well as the sinking of the foundation under the influence of loads that fall from the column to a monolithic foundation and the sinking of the monolithic foundation plate under the influence of loads from the column, on both natural and VAE-reinforced ground